Consumers with bipolar disorder presenting to an Australian child and youth mental health service - McDermott, Brett; Sadhu, Raja; Mayall, Mark (Frontiers in Psychiatry, 2025)
IntroductionThe diagnoses reached for a consecutive set of consumers who presented to a public child and adolescent mental health service (CAMHS) in Australia were reviewed to assess the prevalence of bipolar disorder. Other presentations that had an element of mood elevation, specifically a diagnosis of a manic episode and cyclothymia, were also included.MethodsThis study was a retrospective analysis of consecutive CAMHS consumers between 2014 and 2019. ResultsOf 2131 consumers, the average age was 12.6 years and 2.4% of all first-episode diagnoses were either a manic episode, diagnosis of bipolar disorder, or cyclothymia. This represented approximately 20% of all mood disorder diagnoses. This group did not differ from other consumer presentations on gender, but they were approximately two years older at first episode. No consumer who presented when less than 12 years of age had a diagnosis of bipolar disorder or manic episode. The group were significantly lower on a measure of general psychosocial functioning. The cyclothymia/manic episode/bipolar disorder group was more likely to be admitted to a hospital mental health unit and at some time to be under the mental health act. Over the following five-year period, no patient with cyclothymia was diagnosed with a manic episode or bipolar disorder.DiscussionIn summary, bipolar disorder is an uncommon diagnosis in children and adolescents attending CAMHS in an Australian regional city. However, these consumers are likely to have more psychosocial impairment and require more restrictive care.